Risk taking and gender in hierarchies - Suzanne Scotchmer (Theoretical Economics, 2008)
In a labor market hierarchy, promotions are affected by the noisiness of information about the candidates. I study the hypothesis that males are more risk taking than females, and its implications for rates of promotion and abilities of survivors. I define promotion hierarchies with and without memory, where memory means that promotion depends on the entire history of success. In both types of hierarchies, the surviving risk takers have lower average ability whenever they have a higher survival rate. Further, even if more risk takers than non risk takers are promoted in the beginning of the hierarchy, that will be reversed over time. The risk takers will eventually have a lower survival rate, but higher ability. As a consequence of these differences, the various requirements of employment law cannot simultaneously be satisfied. Further, if promotion standards are chosen to maximize profit, the standards will reflect gender in ways that are difficult to distinguish from discriminatory intent.
Keywords: J7; 330; Labor market hierarchy; promotion; discrimination; affirmative action; hierarchy; risk taking; gender bias